2020
DOI: 10.3390/ijerph17186560
|View full text |Cite
|
Sign up to set email alerts
|

Does Education Moderate the Relationship between Social Capital and Cognitive Function among Older Adults? Evidence from Suzhou City, China

Abstract: While social capital is recognized as an important protective determinant of cognitive function in later life, there is a lack of research examining the potential moderators and mediators in the mechanisms linking social capital to cognitive function. This study investigated the moderating role of education on the relationship between social capital and cognitive function among older adults in urban Chinese communities. Data were derived from a community survey conducted in Suzhou, Jiangsu Province, China, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
3
4
0
Order By: Relevance
“…In order to understand how perceived residential environment quality facilitates urban dwellers’ community identity, based on eudaimonic identity theory, we proposed and tested a conceptual model combining physical dimensions of PREQ indicators with flow and social capital. The reliability and validity of the constructs applied in the present work confirmed previous validation of such tools within the context of Chinese culture: specifically, PREQ indicators (Mao et al, 2015 ); social capital scale (Zhang et al, 2020 ), flow scale (Bonaiuto, Alves, et al, 2016 ; Bonaiuto, Mao, et al, 2016 ); community identity scale (Peng et al, 2021 ). Furthermore, four groups of hypotheses were confirmed in whole or in part, on the basis of a valid sample of 508 residents from 13 residential areas in our sampling city of Chengdu (Sichuan province in China).…”
Section: Discussionsupporting
confidence: 83%
“…In order to understand how perceived residential environment quality facilitates urban dwellers’ community identity, based on eudaimonic identity theory, we proposed and tested a conceptual model combining physical dimensions of PREQ indicators with flow and social capital. The reliability and validity of the constructs applied in the present work confirmed previous validation of such tools within the context of Chinese culture: specifically, PREQ indicators (Mao et al, 2015 ); social capital scale (Zhang et al, 2020 ), flow scale (Bonaiuto, Alves, et al, 2016 ; Bonaiuto, Mao, et al, 2016 ); community identity scale (Peng et al, 2021 ). Furthermore, four groups of hypotheses were confirmed in whole or in part, on the basis of a valid sample of 508 residents from 13 residential areas in our sampling city of Chengdu (Sichuan province in China).…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study showed an association between social capital and successful ageing among empty nesters, meaning that empty nesters with caregiving support, those who belong to an organization in their social network, and those who engage in high levels of reciprocal behaviour are more likely to achieve successful ageing. After adjusting for confounding factors, in the category of social capital, empty nesters with high levels of reciprocal behaviour, who received caregiving support and who belonged to an organization in their social network were more likely to achieve successful ageing, echoing previous findings (Sun et al, 2017; Xue et al, 2020; Zhang, Lu, et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…In this study, the successful ageing rate of empty nesters in China was only 9.2%, which is lower than the successful ageing rates of older adults in other studies in China (14.41% Liu et al, 2017, 17.6% Wu et al, 2017) and other East Asian countries, such as Japan (29.2%) and Korea (25.5%) (Nakagawa et al, 2021). This may be because the population in this study was restricted to empty nesters, who are more prone to physical and mental problems such as dysfunction, dementia (Zeng et al, 2013), and anxiety and depression (Zhang, Lu, et al, 2020) than nonempty nesters due to the lack of adequate family care and spiritual comfort. These problems cause the quality of life of empty nesters to decline, thus affecting the achievement of successful ageing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study manifested that social capital could help older adults continue to independently live in local communities and handle life stressors efficiently, even when they encounter declines in their physical and cognitive health. Social capital can provide older residents with a sense of security and belonging and is an important reserve domain in old age [ 55 ].…”
Section: Discussionmentioning
confidence: 99%